2020
DOI: 10.31578/jebs.v6i1.220
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Perception and Disaster Information of Turkish Secondary School Students*

Abstract: The purpose of this paper is to examine the relationship between the levels of hazard awareness, risk perceptions, the knowledge of response-related protective behavior, and disaster knowledge within the framework of secondary school curriculum in Turkey. A questionnaire examining various measures including hazard awareness, risk perceptions, and general disaster knowledge test was answered by 8th-grade students of schools in Erbaa, Niksar, and Taşova located in North Anatolian Fault Zone (NAFZ) in Turkey. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Pekince concluded that the education program implemented in this study contributed positively to the meta-cognitive awareness skills of the students. In their study on disaster education, Kara and Özdemir (2020) stated that the use of active and participatory teaching methods rather than theoretical approaches is important for obtaining effective learning outcomes.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…Pekince concluded that the education program implemented in this study contributed positively to the meta-cognitive awareness skills of the students. In their study on disaster education, Kara and Özdemir (2020) stated that the use of active and participatory teaching methods rather than theoretical approaches is important for obtaining effective learning outcomes.…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…Undoubtedly, the effects of the Gölcük earthquake on 17 August 1999 (although they did not experience it) affected these children's thinking this way. There is no doubt that the high level of students' perception and fear of earthquake risk is related to the fact that they live in an area with high risk (Kara & Özdemir, 2020). Participants in this study are expected to be concerned about oods, as it is the most common natural disaster ood in Serbia.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that the high level of students' perception and fear of earthquake risk is related to the fact that they live in an area with high risk (Kara & Özdemir, 2020). Participants in this study are expected to be concerned about oods, as it is the most common natural disaster ood in Serbia.…”
Section: Discussionmentioning
confidence: 99%